Workplace design. Issue 3 (7th September 2015) - Karanika-Murray, Maria; Michaelides, George
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Although both job design and its broader context are likely to drive motivation, little is known about the specific workplace characteristics that are important for motivation. The purpose of this paper is to present the Workplace Characteristics Model, which describes the workplace characteristics that can foster motivation, and the corresponding multilevel Workplace Design Questionnaire. Design/methodology/approach – The model is configured as nine workplace attributes describing climate for motivation at two levels, psychological and organizational. The multilevel multi-time questionnaire was validated with data from 4, 287 individuals and 212 workplaces and with integrated regulation as the criterion outcome. Findings – Multilevel factor analysis and regression indicated good internal reliability, construct validity, and stability over time, and excellent concurrent and predictive validity of the questionnaire. Practical implications – The model could help to optimize job and workplace design by contextualizing motivation. The questionnaire offers advancement over single-level climate measures as it is validated simultaneously at two levels. Further research can focus on overcoming the low response rate typical for online surveys, on need fulfillment as the mediating variable, and on the joint influence of job and workplace characteristics on organizational behavior. Originality/value – This work responds to calls to incorporate context in research into organizational behavior and job design. An understanding of the workplace is a first step in this direction. This questionnaire is the first to be validated at multiple levels of analysis. Ultimately, workplace design could support job design and the development of inherently motivating workplaces.